A Review of History of Violence - Alice Horne (Janeway JS, 2019)
Though far from perfect, Lorin Stein’s translation of Édouard Louis’ second novel, History of Violence, is certainly compelling. Read as a “crossing” between languages, the translation can never be a “faithful” equivalent, but it can (and does) allow an Anglophone reader to experience the brutal honesty and raw emotion of Louis’ original.